Pengembangan Alat Militer dalam Al-Qur’an: Pengembangan Interpretasi QS. Al-Anfāl Ayat 60 Berbasis ‘Illat - Abd. Muqit; Alfian Dhany Misbakhuddin; Nashrul Wahyu Suryawan; Dedi Hasnawan; Annas Ma`ruf (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the importance of using ‘illat as a methodological instrument in interpreting Qur’anic verses, particularly in responding to contemporary social dynamics. Through a qualitative approach and literature review of classical and contemporary exegetical methods, the study finds that Muslim scholars have developed approaches such as mafhum muwāfaqah, dalālat al-naṣṣ, and qiyās as means to extend the scope of legal rulings to new cases that share the same ‘illat. A case study of QS. al-Anfāl: 60 demonstrates that the verse is not confined to the historical context of past weaponry, but rather embodies a strategic spirit that remains relevant in the present, including in the form of modern weapons and cyber defense systems. This indicates that Islamic law is dynamic and capable of adapting to changing times, provided that the interpretive process carefully considers the maqāṣid al-sharī‘ah and the principle of ‘illat. The study affirms that ‘illat functions not merely as a legal device, but also as an epistemological principle in constructing interpretations that are relevant and applicable.